2016
DOI: 10.3389/fmicb.2016.00216
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Susceptibility in Serum and Virulence Determinants of Candida Bloodstream Isolates from Hong Kong

Abstract: Candida bloodstream infections (CBI) are one of the most common nosocomial infections globally, and they account for a high mortality rate. The increasing global prevalence of drug-resistant Candida strains has also been posing a challenge to clinicians. In this study, we comprehensively evaluated the biofilm formation and production of hemolysin and proteinase of 63 CBI isolates derived from a hospital setting in Hong Kong as well as their antifungal susceptibility both in the presence and in the absence of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 58 publications
(75 reference statements)
1
16
0
Order By: Relevance
“…In human Candida can cause life threatening systemic infections 49 . Moreover, clinicians have been challenged by the failure of standard antifungal agents.…”
Section: Discussionmentioning
confidence: 99%
“…In human Candida can cause life threatening systemic infections 49 . Moreover, clinicians have been challenged by the failure of standard antifungal agents.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we observed the geometric mean MIC (MIC g ) of 3.48 g/ml for AF 4 against the clinical isolates of C. auris (Table 1), a concentration at which negligible hemolysis was observed. In a recent study from Hong Kong, an alarming rise in resistance has been noted, with 40% of C. albicans, 10% of C. tropicalis, 11.1% of C. parapsilosis, and 100% of C. glabrata strains reported as fluconazole resistant (14). In the present study, fluconazole-resistant C. albicans (n Ï­ 1), C. parapsilosis (n Ï­ 1), and C. krusei (n Ï­ 4) strains displayed MICs of 4, 8, and 4 g/ml, respectively, in the case of AF 4 (see Table S1 in the supplemental material).…”
Section: Discussionmentioning
confidence: 99%
“…C. tropicalis has also been considered a strong biofilm producer species and is highly adherent to epithelial and endothelial cells (Marcos-Zambrano et al, 2014 ). In addition, several recent investigations have reported the recovery of C. tropicalis resistant to the antifungal drugs currently available, such as the azoles derivatives, amphotericin B, and echinocandins (Choi et al, 2016 ; Seneviratne et al, 2016 ). In addition, C. tropicalis has been considered an osmotolerant microorganism and this ability to survive to high salt concentration may be important for fungal persistence in saline environments, contributing to the expression of virulence factors in vitro and resistance to antifungal drugs (Zuza-Alves et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%